INTERPRETASI HADIST TENTANG PERANAN WANITA DALAM DINAMIKA SOSIAL - MS Udin (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2018)
Today, Indonesia is experiencing a crisis in a number of fields. In addition to experiencing the economic crisis, Indonesia is also being hit by a moral, mental and spiritual crisis. Most of the objects which at the same time cause the crisis are women. Starting from pornography cases, showing off bodies, erotic dances, and many more being the main target and the bait is women. Women can be used as resources to improve society. Women can also be a means to destroy and destroy society.Throughout history, women have struggled to get their rights. However, now they are back in colonialism, namely in the form of modernoccupation. Women consider themselves independent when they can show off their beautiful bodies to be enjoyed by masculine men. Women now have forgotten the nature of themselves, they tend to accentuate their facial beauty and beauty without noticing the beauty of their character.